2018
DOI: 10.1101/480350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confidence as a priority signal

Abstract: Correspondence should be sent to aguilarlleyda@gmail.com 5 6When dealing with multiple tasks, we often find ourselves in the problem of 7 establishing the order in which to tackle them. Here we show that confidence, the 8 subjective feeling in the accuracy of our decisions or actions, plays an active role in 9 task ordering. Our participants categorized perceptual stimuli along two dimensions 10 and reported the confidence on each decision, while we manipulated the difficulty 11 over each dimension independent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Accurate metacognition is important in many domains such as successful learning (Aguilar-Lleyda et al, 2020;Hainguerlot et al, 2018;Schunk & Ertmer, 2000) and the ability to engage in sequential decisions (van den Berg et al, 2016). However, despite its importance, metacognition is often found to be inefficient (Fleming et al, 2010;Maniscalco & Lau, 2012;Metcalfe & Shimamura, 1994;Shekhar & Rahnev, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate metacognition is important in many domains such as successful learning (Aguilar-Lleyda et al, 2020;Hainguerlot et al, 2018;Schunk & Ertmer, 2000) and the ability to engage in sequential decisions (van den Berg et al, 2016). However, despite its importance, metacognition is often found to be inefficient (Fleming et al, 2010;Maniscalco & Lau, 2012;Metcalfe & Shimamura, 1994;Shekhar & Rahnev, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, metacognition plays both monitoring and regulatory roles (Nelson & Narens, 1990). Research on visual metacognition has paid little attention to its specific functions, although it has been suggested that perceptual confidence might guide perceptual learning (Guggenmos et al, 2016), associative learning (Hainguerlot et al, 2018), task prioritization (Aguilar-Lleyda et al, 2020), and moderate sensory-evidence accumulation (Balsdon et al, 2020). However, in most studies, visual metacognition has not been directly manipulated, which leaves the causal role of metacognition in behavior unclear.…”
Section: Long-term Goals For the Field Of Visual Metacognitionmentioning
confidence: 99%
“…Hainguerlot, Vergnaud, & de Gardelle, 2018), allocate resources to a particular task (e.g. van den Berg et al, 2016), compare different tasks (de Gardelle & Mamassian, 2014) and prioritize them (Aguilar-Lleyda, Lemarchand, & de Gardelle, 2020). Perceptual confidence, and more broadly metacognition, has been extensively reviewed elsewhere (e.g.…”
Section: Introductionmentioning
confidence: 99%